Knowledge Donating And Its Impact On Collective Intelligence: Sociolinguistic Analytical Study Of Arab Employees At Al-Rajhi Bank - Alhamdi, Fuad Mohammed (Ijaz Arabi Journal of Arabic Learning, 2024)
The current research aims to measure knowledge donation's role in collective intelligence, represented by the dimensions. The researcher distributed (125) questionnaires to a sample of Al-Rajhi Bank employees in Riyadh, and (102) analysis forms were adopted. To draw the results, the researcher used Several statistical methods such as normal distribution, Cronbach’s alpha stability coefficient, arithmetic mean, standard deviation, and structural equation modeling. The researcher reached a set of results, including that Al-Rajhi Bank's interest in encouraging its employees to share knowledge among them contributes to developing their collective intelligence by improving their mental abilities to present new creative ideas that serve the interest. Implementing training and development programs: the bank can provide training and development programs for its employees to improve their Arabic language skills and ensure their ability to communicate effectively with customers. In addition, the researcher presented several recommendations, including the fact that Al-Rajhi Bank's keenness to share knowledge requires them to urge employees to participate in training workshops to improve their cognitive and mental abilities—improving the bank's performance in its various branches.